Brook Trout Movement and Survival in the West Branch of the Wolf River, Wisconsin - Easterly, Emma G. (University of Wisconsin-Stevens Point, College of Natural Resources, 2018)
A 21 km stretch of the West Branch of the Wolf River (WBWR), a tributary to the Wolf River, traversing the Menominee Indian Reservation in central Wisconsin is designated as a class I trout stream with naturally-reproducing brook trout Salvelinus fontinalis. Brook trout are the only stream trout (technically, a charr) native to Wisconsin. Because many anglers target brook trout, they are considered a highly sought-after sport fish and are intensively managed via harvest regulations and habitat improvement efforts. Previous research on fish movement has focused largely on highly migratory and anadromous fish species, but fish in smaller stream systems can also exhibit extensive movements. Movement of brook trout throughout a system can affect management decisions. There are various factors affecting connectivity within a stream, the foremost factor being the construction or removal of dams. In 2015, the Menominee Indian Tribe removed two dams and constructed new channels with graded steps to promote upstream and downstream movement of fish in the WBWR. These changes may have affected brook trout movements by providing greater access to different portions of the river, including access to lacustrine habitats provided by Upper Bass Lake and the Neopit Mill Pond located at the upper and lower ends of the river segment. Little is known regarding movement of brook trout within this section of the WBWR and seasonal movements could have important implications for future management and stream restoration. The objectives of my study were to determine if: 1) brook trout use multiple river segments during the year, including sections of the stream where two dams were removed and channel alterations occurred; 2) brook trout enter Upper Bass Lake and the Neopit Mill Pond as seasonal refuges, but eventually return to the WBWR; 3) a rapids located just upstream from the Neopit Mill Pond acts as an upstream and downstream barrier to movement; 4) annual survival rates are comparable to other brook trout populations; and 5) relative abundance estimates are comparable to statewide Wisconsin trout streams. Between 2016 and 2018, a total of 920 brook trout were captured using barge and backpack electroshocking at various locations throughout the WBWR. Brook trout ≥ 120 mm total length (TL) were implanted with 12-mm passive integrated transponder (PIT) tags and brook trout ≥ 254 mm were implanted with 23-mm PIT tags. Of the 920 captured brook trout, a total of 447 brook trout were implanted with PIT tags. In 2016 (13 October - 17 November), three paired stationary PIT antennas were deployed in the WBWR and during 2017 (April – 6 December) four antennas were installed in the stream. Locations for installation were based on ability to effectively address the project objectives and access to the river. Data were downloaded from these antenna installations on a weekly basis. Upstream and downstream movement during the year was minimal, with the majority of brook trout remaining in the river sections they were tagged in. Use of Upper Bass Lake and the Mill Pond was also minimal, with < 5% of tagged brook trout entering either of these habitats. Movement (both upstream and downstream) through the rapids located just before the Mill Pond was observed, with three fish moving downstream through the rapids and then returning upstream through the rapids into the WBWR. The low percentage of detections suggests that the brook trout within the WBWR display limited movement. Low occurrence of detections paired with low physical recaptures and an eight month survival rate of 0.27, suggests brook trout in the WBWR experience high mortality rates, which is consistent with previous assessments. Furthermore, average catch per unit effort (CPUE; fish/km) for all brook trout at all sampling stations was 68 ± 22 brook trout per km (114 per mile) placing this section of the WBWR within the 60th percentile of all statewide trout streams and within the 50th percentile for all statewide class I trout streams. Future research within this system should focus on determining if high mortality is a factor regulating brook trout abundance in the WBWR and whether exploitation (current harvest regulation is 20/day, 6-inch minimum) is a significant component of this mortality. Understanding these mortality components would help determine if the WBWR brook trout population would benefit by implementing more conservative harvest regulations.